2017
DOI: 10.7759/cureus.1729
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Compression Fractures after Lumbar Instrumentation

Abstract: Lumbar spinal stenosis (LSS) is primarily found in an older population. This is a similar demographic group that develops both osteoporosis and vertebral compression fractures (VCF). This report reviewed a series of patients treated for VCF that had previous lumbar surgery for symptomatic spinal stenosis. Patients that only underwent laminectomy or fusion without instrumentation had a similar distribution of VCF as the non-surgical population in the mid-thoracic, or lower thoracic and upper lumbar spine. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Thoraco-lumbar osteoporotic compression fractures have the highest risk of continued collapse because of their location at the mobile junction between the thoracic and lumbar spine which has the largest degree of motion of the spine [1]. Fractures in this area are also seen frequently after previous lumbar fusion or stabilization, as in this patient, with a previous L4-5 stabilization device [2]. A number of studies have found that patients with intradiscal and intra-vertebral vacuum clefts on computed tomography (CT) or magnetic resonance imaging (MRI), as in this patient, are also at a significantly higher risk of continued collapse even with kyphoplasty (KP) and especially if the cleft is not filled with cement at the time of the procedure [3-4].…”
Section: Introductionmentioning
confidence: 99%
“…Thoraco-lumbar osteoporotic compression fractures have the highest risk of continued collapse because of their location at the mobile junction between the thoracic and lumbar spine which has the largest degree of motion of the spine [1]. Fractures in this area are also seen frequently after previous lumbar fusion or stabilization, as in this patient, with a previous L4-5 stabilization device [2]. A number of studies have found that patients with intradiscal and intra-vertebral vacuum clefts on computed tomography (CT) or magnetic resonance imaging (MRI), as in this patient, are also at a significantly higher risk of continued collapse even with kyphoplasty (KP) and especially if the cleft is not filled with cement at the time of the procedure [3-4].…”
Section: Introductionmentioning
confidence: 99%
“…Since VCFs occur in an older population, these same patients often have concurrent lumbar degenerative osteoarthritis, spondylolisthesis, and stenosis, so care needs to be taken in reviewing symptoms as well as radiologic studies for lumbar pain after a minor fall or accident [ 12 ]. Patients with previous lumbar surgery and fusions, especially with spinal instrumentation, are more prone to developing a VCF above the fusion, which may not be initially recognized, as attention is focused on the previous lumbar surgery [ 13 ]. In these cases, it will be the persistence of pain despite physical therapy or a recognition that the pain is in a different location than the lower lumbar spine in combination with new radiologic tests demonstrating a VCF that leads to the fracture being recognized as a cause of the pain.…”
Section: Discussionmentioning
confidence: 99%
“…This progression is a result of the lateral load shift and uneven axial load bearing on weakened cancellous bone at the adjacent vertebra and sacral alae [ 27 ]. Patient comorbidities, chronic steroid use, and especially non-compliance with medication and lack of bracing are additional factors that contribute to progressive deterioration with multiple recurrent lumbar fractures [ 29 - 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…In some of these patients, there may be a role for preventive vertebroplasty to decrease the chance of future cascading fractures [ 36 - 38 ]. If the lumbar curve continues to progress and especially if there is radiculopathy associated with lumbar stenosis or degenerative spondylolisthesis, decompression with multilevel screw fixation is an option [ 30 ]. However, since the vertebrae in these patients are severely osteoporotic, over multiple levels, screw fixation may need to include supplemental bone cement and the use of multilevel bicortical screws that avoid the cancellous bone and take purchase on the vertebral endplate cortex [ 39 ].…”
Section: Reviewmentioning
confidence: 99%